Adaptation of microcystin thiol derivatization for matrix-assisted laser desorption/ionization-time of flight (MALDI-TOF) mass spectrometry analysis. (January 2016) - Puddick, Jonathan; Miles, Christopher O.; Prinsep, Michèle R.
Abstract: Thiol derivatization of microcystins is an emerging technique for simplifying mass spectrometric analysis of microcystins in complex matrices and for distinguishing between Mdha-/Dhb-containing microcystins. The present protocol is not compatible with MALDI-TOF mass spectrometry, but use of sodium carbonate buffer and desalting with ZipTips yielded no loss in sensitivity. Use of ammonium carbonate buffer followed by dilution in MALDI matrix resulted in a small loss of sensitivity but allowed accurate determination of reaction rates. Graphical abstract: Highlights: ZipTip clean-up of samples allowed MALDI-TOF analysis with no loss in sensitivity. Thiol derivatization using (NH4 )2 CO3 allowed MALDI-TOF analysis without clean-up. Derivatization rates could be measured as reaction was halted by the MALDI matrix.